Criminal Law Study on Narcotics Abuse Rehabilitation - Salma Widiasyam; Oheo K. Haris; Sitti Aisah Abdullah (Universitas Negeri Semarang, 2020)
The purpose of this research is to determine whether the rehabilitation of the victims of narcotics abuse in the decree of the District Court of Kendari No. 236/Pid. Sus/2019/PN K has fulfilled the element of Article 54 Act number 35 year 2009. The type of research used in this study is normative research, using the Statute Approach, Case Approach, Conceptual Approach. Based on the results the authors conclude that narcotic addicts and narcotics abuse victims are obliged to undergo medical rehabilitation and social rehabilitation. The judge in the its verdict prosecute convicted because it has been proven legally and committed guilty of committing a criminal offence